Perancangan Buku Komik Edukasi Tentang Kesehatan Pencernaan pada Anak Usia 8-12 Tahun - Fany, John; Putrinda, Tisa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Health is the most important aspect for every human being. As much as 80% of the immune system is found in the digestive tract, so maintaining digestive health is crucial for overall body health. Every child experiences significant growth during their development. This significant growth is also influenced by daily food consumption. Health education is important in one of the efforts to learn a healthy lifestyle. The goal of this research is to design an educational medium in the form of a comic book and to create effective promotional media for the comic book. The research method used in this design process is qualitative method. Data collection methods are carried out through literature study, observation methods, and interviews. The data analysis technique used is qualitative data analysis with stages of data reduction, data presentation, and conclusion drawing. Comic books can be an effective medium for teaching values or new knowledge to children in a light and easily understood manner. An educational comic about digestive health is needed that can be read by children aged 8-12 years. This research aims to understand the process of designing an educational comic for children. The design of the educational comic 'Adventures in the Land of Gutopia' is expected to serve as an engaging and educational tool for children in promotional media.